Small RNAs induce the activation of the pro‐inflammatory TLR7 signaling pathway in aged rat kidney. Issue 5 (30th June 2017) - Lee, Eun Kyeong; Chung, Ki Wung; Kim, Ye Ra; Ha, Sugyeong; Kim, Sung Dae; Kim, Dae Hyun; Jung, Kyung Jin; Lee, Bonggi; Im, Eunok; Yu, Byung Pal; Chung, Hae Young
Summary: We have recently reported that TLR‐related genes, including TLR7, are upregulated during aging. However, the role of TLR7 and its endogenous ligand in inflammation related to aging is not well defined. Here, we established that small RNAs trigger age‐related renal inflammation via TLR7 signaling pathway. We first investigated the expression changes of nine different TLRs in kidney of 6‐month‐old young rats and 20‐month‐old aged rats. The results revealed that the expression of TLR7 was the highest among nine TLRs in kidney of old rats compared to the young aged rats. Next, to assess the role of cellular RNA as a TLR7 ligand, we treated a renal tubular epithelial cell line with total RNA isolated from the kidney of young and old rats. The results showed that RNA isolated from old rats showed higher expression of TLR7, IL1β, and TNFα compared to that from young rats. Furthermore, RNA isolated from old rats induced IKKα/β/JNK/NF‐κB activation. To identify RNA that activates TLR7, we isolated small and large RNAs from old rat kidney and found that small RNAs increased TLR7 expression in cells. Finally, to investigate the local inflammatory response by small RNA, C57B/L6 mice were intraperitoneally injected with small RNAs isolated from young and old rats; thereby, RNA isolated from old rats induced higher inflammatory responses. Our study demonstrates that renal small RNAs from aged rats induce pro‐inflammatory processes via the activation of the TLR7/IKKα/β/JNK/NF‐κB signaling pathway, and highlights its causative role as a possible therapeutic target in age‐related chronic renal inflammation.